Four kinds of the two-equation turbulence model's research on flow field simulation performance of DPF's porous media and swirl-type regeneration burner. (25th January 2016) - Fu, Jun; Tang, Yuan; Li, Jianxing; Ma, Yi; Chen, Wei; Li, Hong
Highlights: Swirl-type burner was introduced to regeneration diesel particulate filter. Flow field of swirl and porous media was coupling simulated. Four commonly used two-equation turbulence models were compared. Comprehensive simulation performances of the models were analyzed. SST k-ω model can better agree with the experiments as a whole. Abstract: The flow field of the diesel particulate filter (DPF) with porous media and the swirl regeneration burner is complex, so which kind of turbulence model to be chosen has a great influence on the accuracy and performance on the computational fluid dynamics (CFD) simulation. Based on Fluent software and with the same conditions, the standard k − ε, RNG k − ε, Realizable k − ε and SST k − ω turbulence models were adopted to get the back-flow characteristics and the distribution of velocity, pressure and turbulent kinetic energy in the swirl burner and the porous media, then the results were compared and analyzed. It shows that, at the sudden expansion zones and near-wall region, the flow characteristics and back-flow features of the Realizable k − ε model are clearer than that of the standard k − ε model and the RNG k − ε model, and the maximum peaks of turbulent kinetic energy and the larger gradient are gotten by the RNG k − ε model, but better back-flow characteristics and more abundant details of flow field by the SST k − ω model, and the center average velocity and pressure at the inlet and outlet all agreed well with experiments.